2017
DOI: 10.1097/md.0000000000006490
|View full text |Cite
|
Sign up to set email alerts
|

Warming infusion improves perioperative outcomes of elderly patients who underwent bilateral hip replacement

Abstract: Background:This prospective, randomized, and controlled study was performed to determine the benefits of prewarmed infusion in elderly patients who underwent bilateral hip replacement.Methods:Between September 2015 and April 2016, elderly patients who underwent bilateral hips replacement that met the inclusion and exclusion criteria were included in this study. After inclusion, patients were randomized into one of the study groups: in the control group, patients received an infusion of fluid kept at room tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Core temperature should be monitored in operations lasting more than 30 min, and warming should be used in older patients [72]. A forced-air warming system set at 42 °C is the most effective means of rewarming older patients with postoperative hypothermia [122], but a prewarmed infusion could also reduce the incidence of perioperative hypothermia and improve outcomes in geriatric patients [123].…”
Section: Strength Of Recommendationmentioning
confidence: 99%
“…Core temperature should be monitored in operations lasting more than 30 min, and warming should be used in older patients [72]. A forced-air warming system set at 42 °C is the most effective means of rewarming older patients with postoperative hypothermia [122], but a prewarmed infusion could also reduce the incidence of perioperative hypothermia and improve outcomes in geriatric patients [123].…”
Section: Strength Of Recommendationmentioning
confidence: 99%
“…Meanwhile, hypothermia might be associated with increased risk of several different kinds of adverse events. For instance, morbid cardiac events and ventricular tachycardia, blood loss, wound infections, delayed post-anesthetic recovery time and hospitalization, and postoperative cognitive dysfunction [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis has shown that the use of monitoring with BIS reduced extubation time, orientation time and PACU LOS [ 19 ]. Also, warming to prevent perioperative hypothermia has been reported to reduce the extubation time and improve outcomes in the elderly during lengthy surgery [ 20 ]. However, it is worth mentioning that the anesthesia care made by the treating anesthetists in the control group was optional.…”
Section: Discussionmentioning
confidence: 99%